Ghrelin signaling in the gut, its physiological properties, and therapeutic potential. Issue 9 (1st August 2013) - Avau, B.; Carbone, F.; Tack, J.; Depoortere, I.
Abstract Background Ghrelin, an orexigenic hormone secreted from the stomach, was soon after its discovery hypothesized to be a prokinetic agent, due to its homology to motilin. Studies in animals and humans, using ghrelin and ghrelin receptor agonists, confirmed this hypothesis, suggesting a therapeutic potential for the ghrelin receptor in the treatment of gastrointestinal motility disorders. Precilinical studies demonstrated that ghrelin can act directly on ghrelin receptors on the enteric nervous system, but the predominant route of action under physiological circumstances is signaling via the vagus nerve in the upper gastrointestinal tract and the pelvic nerves in the colon. Different pharmaceutical companies have designed stable ghrelin mimetics that revealed promising results in trials for the treatment of diabetic gastroparesis and post‐operative ileus. Nevertheless, no drug was able to reach the market so far, facing problems proving superiority over placebo treatment in larger trials. Purpose This review aims to summarize the road that led to the current knowledge concerning the prokinetic properties of ghrelin with a focus on the therapeutic potential of ghrelin receptor agonists in the treatment of hypomotility disorders. In addition, we outline some of the problems that could be at the basis of the negative outcome of the trials with ghrelin agonists and question whether the right target groups were selected. It is clear that a new approach is needed to develop marketable drugs with this class of gastroprokinetic agents.